TRAINING COURSE ON DELIVERY CARE AND NEONATAL CARE IN RURAL HOSPITALS, GEZIRA STATE, SUDAN - Elsanousi, Mohamed; A. Mirghani, Omer; Sid Ahmed, Mohamed A.; Bashar, Zahra (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
This paper describes a training course for medical officers working in the rural hospitals in Gezira State to achieve a general objective; safe management of obstetric emergencies, miscarriage and the newborn . the description of the course includes; an introduction, the specific learning objectives, a detailed plan of work, instructional methods, resources , the course timetable, evaluation methods, description of the logbook and the feedback questionnaire. This article also includes descriptions of our experience in three rounds during which 43 medical officesr were trained